Listening In : Radio and the American Imagination. - Douglas, Susan J. (University of Minnesota Press, 2004)
In Listening In, Susan Douglas explores how listening has altered our day-to-day experiences and our own generational identities, cultivating different modes of listening in different eras; how radio has shaped our views of race, gender roles, ethnic barriers, family dynamics, leadership, and the generation gap. With her trademark wit, Douglas has created an eminently readable cultural history of radio.